Evidence of the 4is of organizational learning in leadership development - Prado, Gladys Milenna; de Mello, Marta Inês Caldart de Mello; Steil, Andrea Valeria (Seven Editora, 2023)
Organizational Learning (OL) and leadership development (DL) are topics related to behavior change in organizations. We did not find studies that show the relationship between OL based on the 4Is Framework processes and DL. The objective of the article is to identify evidence of the psychological and social processes of OL found in the reports of results obtained in DL actions promoted within organizations. A narrative literature review, with a structured search and application of inclusion and exclusion criteria and thematic analysis were used. Initial evidence that associates OL with DL and characteristics found for each of the 4Is processes are presented. The findings suggest as evidence cognitive and behavioral changes caused by DL actions, which in turn, generated changes in organizational culture, such as the adoption of new practices and routines.DOI:https://doi.org/10.56238/alookdevelopv1-040